Identification of donor parents containing favourable alleles for improving target American cotton hybrid (NA 1325 × L 604) - B, BALAKRISHNA; V, CHENGA REDDY; REDDY, K V SIVA; SATISH, Y; REDDY, K BAYYAPU (The Indian Journal of Agricultural Sciences, 2023)
The present study was conducted during kharif 2013, kharif 2014 and kharif 2015 at Regional Agricultural Research Station, Lam, Guntur, Andhra Pradesh, India. The aim of the present investigation was to evaluate four American cotton genotypes and to determine which have the greatest relative values of favourable alleles for the improvement of number of bolls/plant, boll weight (g), 2.5% span length (mm), bundle strength (g/tex), seed cotton yield/plant (g) and lint yield/plant (g) in the elite single cross cotton hybrid (NA 1325 × L 604). Based on the estimates of μG’ values the genotype Surabhi was noted with positive high μG’ value and may be used as source of favourable alleles for improving elite hybrid with respect to quality traits like bundle strength (μG’=1.830*) and 2.5% span length (μG’=1.325*). This improvement may be possible by transferring favourable alleles from Surabhi to NA 1325 through back crossing as it had high genetic affinity with NA 1325. For number of bolls/plant RAH 1004 (μG’=3.230*) and HYPS 152 (μG’=0.302*) for boll weight and both the donors for seed cotton yield/plant (μG’ RAH 1004=13.915*and μG’ HYPS 152=23.972*) may be used as donors as they recorded significant and positive μG’ estimates.